Chromium allergy and dermatitis: prevalence and main findings. (24th June 2015) - Bregnbak, David; Johansen, Jeanne D.; Jellesen, Morten S.; Zachariae, Claus; Menné, Torkil; Thyssen, Jacob P.
Summary The history of chromium as an allergen goes back more than a century, and includes an interventional success with national legislation that led to significant changes in the epidemiology of chromium allergy in construction workers. The 2015 EU Leather Regulation once again put a focus on chromium allergy, emphasizing that the investigation of chromium allergy is still far from complete. Our review article on chromium focuses on the allergen's chemical properties, its potential exposure sources, and the allergen's interaction with the skin, and also provides an overview of the regulations, and analyses the epidemiological pattern between nations and across continents. We provide an update on the allergen from a dermatological point of view, and conclude that much still remains to be discovered about the allergen, and that continued surveillance of exposure sources and prevalence rates is necessary.